Topology Optimization Design of Transfer Case Housing - Zhang Qing; Zhang Bin; Li Hongbiao; Huo Chunjing; Yang Xianxue (Jixie chuandong)
The topology optimization design of the complicated transfer case housing is conducted by using the variable density method. Taking the minimum compliance as the optimization objective and the volume fraction,static displacement,static stress,modal frequency and machining process as constrains condition,the topology optimization analysis of external shape and internal rib plate are carried out. Then,the static strength and modal character analysis of the optimized transfer case housing are carried out. The analysis results demonstrate that the static strength and modal frequency are higher than the design objective,the topology optimization design of complex housing structure is realized.